Impact of an Innovative Educational Strategy on Medication Appropriate Use and Length of Stay in Elderly Patients. Issue 24 (June 2015) - Corbi, Graziamaria; Gambassi, Giovanni; Pagano, Gennaro; Russomanno, Giusy; Conti, Valeria; Rengo, Giuseppe; Leosco, Dario; Bernabei, Roberto; Filippelli, Amelia; Ferrara, Nicola; Wang., Hsueh
<x xml:space="preserve">Abstract</x> Abstract To evaluate the impact of an educational strategy on potentially inappropriate medications (PIMs) and length of stay in hospitalized elderly patients. Design: An open study, with two cross-sectional surveys interspersed with an educational program (PRE phase and POST phase), has been performed in order to compare the PIMs number before and after the introduction of an educational strategy. The study included 2 phases: PRE, in which patients were enrolled as control group; POST, in which an educational strategy on the PIMs use was introduced among physicians, and patients were enrolled as intervention group. Setting: Italian residential rehabilitation Centre. Inclusion criteria were ≥2 active chronic diseases and the current use of ≥4 medications. The educational strategy consisted of a 3-day course on strategies to prevent PIMs and a computerized tool running on a Personal Digital Assistant (PDA) device to check for PIMs. Outcomes: The primary was the PIMs number, the secondary the length of stay. Results: A total of 790 patients, 450 controls and 340 cases, were enrolled. According to the Beers criteria, 52.3% of the study population received ≥1 PIMs, 18.73% ≥2, and 2.4% ≥4 PIMs. A significant reduction of PIMs (P = 0.020) and length of stay (P < 0.0001) were seen in the intervention group. At multivariate analysis, PIMs significantly correlated with age, drugs number, and the intervention, and the length of stay significantly correlated with disease count, comorbidities, and intervention. These data suggest that our educative instrument may be useful in reducing the PIMs number and length of hospitalization in elderly with a high number of drugs and comorbidities.